Diagnostics of the technical condition of load-bearing structures of an old building - Sazonova Svetlana; Anikeev Evgeny; Shcherbakova Irina; Chernikov Eduard; Nikolenko Sergey (E3S Web of Conferences)
The paper considers the process of examining the current state of materials and load-bearing structures of an old building. Such buildings are often located in a forest complex. Recommendations to eliminate the defects and damage identified as a result of the survey, as well as the possibility of increasing the number of storeys were made. The process of examining the main part of the building, which is complex in terms of shape and is under the influence of the external environment of the forest complex, is considered. The design feature of the building is studied. The results of visual and instrumental inspection of the building are presented. The main recommendations for the elimination of defects and damages are developed and given. It is noted that the technical examination of the old building by the method of non-destructive testing showed that the state of the building structures of the building at the time of the survey was limited in working capacity.